2012
DOI: 10.1002/jbm.a.33310
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the effect of amphiphilic siloxane oligomers on dermal fibroblasts

Abstract: This study investigates the effect of well-defined poly(dimethylsiloxane)-poly(ethylene glycol) (PDMS-PEG) ABA linear block co-oligomers on the proliferation of human dermal fibroblasts. The co-oligomers assessed ranged in molecular weight (MW) from 1335 to 5208 Da and hydrophilic-lipophilic balance (HLB) from 5.9 to 16.6 by varying the number of both PDMS and PEG units. In general, it was found that co-oligomers of low MW or intermediate hydrophilicity significantly reduced fibroblast proliferation. A linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Farrugia et al investigated the effect of well-defined poly(dimethylsiloxane)-poly(ethylene glycol) (PDMSPEG) ABA linear block co-oligomers on the proliferation of human dermal fibroblasts. 50 The co-oligomers assessed, ranged in molecular weight (MW) from 1335 to 5208 Da and hydrophilic-lipophilic balance (HLB) from 5.9 to 16.6 by varying the number of both PDMS and PEG units. In general, it was found that co-oligomers of low MW or intermediate hydrophilicity, significantly reduced fibroblast proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Farrugia et al investigated the effect of well-defined poly(dimethylsiloxane)-poly(ethylene glycol) (PDMSPEG) ABA linear block co-oligomers on the proliferation of human dermal fibroblasts. 50 The co-oligomers assessed, ranged in molecular weight (MW) from 1335 to 5208 Da and hydrophilic-lipophilic balance (HLB) from 5.9 to 16.6 by varying the number of both PDMS and PEG units. In general, it was found that co-oligomers of low MW or intermediate hydrophilicity, significantly reduced fibroblast proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Allyl-MPEG was prepared by the chemical reaction between the terminal hydroxyl groups of MPEG and allyl bromide under the catalysis of NaH . The NaH suspension (0.50 g in 5 mL of THF) was added in dried THF solution (30 mL) with the dissolution of MPEG (14.70 g, 7.35 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…The triblock copolymer was synthesized by hydrosilylation reaction of the obtained allyl-MPEG and PDMS products according to the previous protocol . Allyl-MPEG (6.74 g, 330 mmol) was dissolved in toluene (4 mL) and then the Speier’s catalyst (12 μL) was added under magnetic stirring for 20 min at 90 °C under the protection of nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
“…α,ω‐Dihydro(polydimethylsiloxane) ( 1 ) was prepared according to the procedures as described previously . Allyl amine (8.55 g, 150 mmol) and 1 (25.0 g, 29.8 mmol, M n = 840) were dissolved in toluene (30 mL).…”
Section: Methodsmentioning
confidence: 99%